The application of exopolysaccharides (EPS) can prevent viral disease of fish. - Bergmann, Sven Michael; Reichert, Matthias; Hwang, J; Becker, Anna; Lenk, Matthias; Kotterba, Günter; Buchholz, Rainer; Jung, Sunhwa; Gebler, A; Todte, M; Kielpinska, J; Lindenberger, Christoph (Bulletin of the European Association of Fish Pathologists, 2022)
In the frame of investigations on the use of exopolysaccharides (EPS) from Arthrospira platensis in carp and koi cultures, two animal experiments were carried out to assess their efficiency as prophylactic and metaphylactic (therapeutic) measures against koi herpesvirus disease (KHVD). In experiment 1, carp were treated with algae biomass (BM) and EPS before and after infection with European lineage koi herpesvirus (KHV-E). In experiment 2, carp were treated with EPS prior and after the infection with Taiwan isolate of KHV (KHV-T), only prior to infection with higher concentration of EPS or only after the infection with KHV-T. No conclusive protection against KHV was observed in experiment 1 in carp treated with BM. In groups where EPS was applied, carp were protected to a certain extent. In experiment 2, carp were protected significantly against a severe KHVD outbreak. In the prophylactic group, which received a double EPS concentration for six weeks, and in the metaphylactic group, KHVD was stopped. Fish developed antibodies against EPS as well as against KHV at day 30 post infection.<br
Keywords: algae; EPS; KHV; KHVD; inhibition; prophylaxis; metaphylaxis